(untitled) (Third Sector Social Economic Review, 2024)
Cooperatives are organizations that help people meet their daily human needs through solidarity when they cannot meet them alone. Cooperatives established and run by women are called women’s cooperatives. It is as important for cooperatives to be effective and efficient as it is for them to be established. The aim of this research is to reveal the perspectives of women cooperative members towards cooperatives. The research field is the Antalya Village Market, which was opened with the aim of establishing women’s cooperatives and supporting women farmers under the agreement signed between Antalya Kepez Municipality and Antalya Provincial Directorate of Agriculture and Forestry. Within the scope of the study, in-depth interviews, a qualitative data collection method, were used. During the interviews, closed-ended and open-ended questions were asked to cooperative managers and cooperative member women. The findings revealed that the expectations of cooperative managers and cooperative members were not consistent, the training and feasibility services provided by cooperatives were not consistent with the training and feasibility services provided by members, cooperatives benefited from public support while members did not, and managers’ reasons for forming cooperatives were consistent with members’ reasons for finding cooperatives successful. Six themes emerged from the open-ended questions asked of women cooperative members. From these themes, it was concluded that cooperative members define cooperatives as ""cooperation and solidarity"", that members do not face any barriers in the labor market, that members join cooperatives mostly to ""increase sales potential"", that members do not experience gender discrimination prior to cooperative membership, that members are not aware of public support, and that members have demands for increased public support.